Corrosive effects of smoke with different concentrations from PVC on 304 stainless steel and 6061 aluminium alloy. (17th February 2018) - Liu, Xufei; Xu, Mingjun; Lu, Shouxiang; Liew, Kim Meow
ABSTRACT: Three hundred and four stainless steel and 6061 aluminium alloy samples were exposed to different concentrations of smoke generated by polyvinyl chloride in high humidity. The corrosion kinetics of 304 stainless steel and 6061 aluminium alloy under smoke were found to obey the power function and a linear rule, respectively. Pitting corrosion in smoke became increasingly obvious with exposure time. Surface morphology and chemical compositions of corrosion products were analysed by scanning electron microscope, energy dispersive spectroscopy and X-ray photoelectron spectroscopy. Possible corrosion mechanisms were proposed and compared. All the analysis helps to provide basic information for the determination of smoke damage and timely rescue after fire.